The Effect of Carbon Emission Disclosure, Green Accounting, and Institutional Ownership on Firm Value - Siswati, Catur Rekno; Sumayyah (Research Horizon, 2025)
The mining sector faces increasing pressure to balance financial performance with environmental responsibility, influencing investor perceptions and company value. This study aims to examine the impact of carbon emission disclosure, green accounting, and institutional ownership on the value of mining companies listed on the Indonesia Stock Exchange during 2021–2024, grounded in stakeholder theory. A quantitative approach with a causal associative design was employed, using secondary data from annual, financial, and sustainability reports of 15 mining companies, yielding 60 observations selected through purposive sampling. Data were analyzed using multiple linear regression and classical assumption tests via SPSS 25. Findings reveal that carbon emission disclosure and green accounting do not significantly affect company value, with coefficients of 0.025 (significance 0.918) and -0.078 (significance 0.618), respectively. However, institutional ownership has a significant positive effect, with a coefficient of 1.005 (significance 0.004). Collectively, these variables significantly influence company value (F-test significance 0.008). The results suggest that investors prioritize governance mechanisms over environmental performance, highlighting the need for enhanced governance to boost company value.